Blurring the Relationship Boundaries between Women and Technology - Retno Widyastuti, Dhyah Ayu; Wahyuni, Hermin Indah; Wastutiningsih, Sri Peni (Jurnal The Messenger, 2023)
Introduction: Technology penetrates society and has an impact on daily life. Historically, technology was dominated by men. Recently, women have become closer to the internet to share ideas through cyberspace, build sites that allow them to interact with women and women’s communities, and use the internet to help their productive activities. This study attempts to explain modern society’s connections between women and technology. The data analysis used cyberfeminism theory. Methods: This study used qualitative methods and illustrated the case study of SiBakul platform usage by MSMEs in the Special Region of Yogyakarta. SiBakul is an ICT-based platform for branding the digital ecosystem of MSMEs in DIY Province. The data collection employed in-depth interviews, observation, and documentation. Data sources include MSME actors and the government responsible for the MSME sector.  Findings: The results showed that SiBakul is the driving force behind digital platforms that support MSMEs' activities. Through the marketplace, the MSME actors, both women and men, use technology. The analysis concludes that there is a possible equality between women and men in accessing and using technology to promote and market their business products. The women develop their insight into cyberspace to increase their knowledge and be more productive economically. Originality: The study uses the cyberfeminism perspective to highlight the importance of adapting to environmental changes in the Industry 4.0 era with women's equality for broader access to technology. Besides, it is considered for women’s equality in public areas and the productive sector, such as in MSME activities.